Catalytic bromate reduction in water: Influence of carbon support. Issue 3 (June 2019) - Soares, O.S.G.P.; Ramalho, P.S.F.; Fernandes, A.; Órfão, J.J.M.; Pereira, M.F.R.
Graphical abstract: Highlights: Bromate reduction with H2 over Pd and PdCu catalysts supported on carbon nanotubes (CNT). CNTs with different textural and surface chemical properties were used as support. CNT properties, as metal support, have a relevant role in the bromate reduction. Catalytic activity trend: N-doped CNT > basic CNT > acid CNT. Abstract: The classification of bromate as possibly carcinogenic for humans has led to an increasing interest of researchers in the development of effective technologies for its removal from water. Catalytic reduction of bromate into bromide in water under hydrogen flow was studied in detail using Pd and PdCu catalysts supported on multi walled carbon nanotubes with different textural and surface chemical properties. Cu supported catalysts show poor catalytic activity, whereas the coupling of Cu and Pd does not improve the catalytic performance of the Pd supported catalysts, the exception being the bimetallic catalysts supported on CNT-BM-U (sample N-doped using urea as nitrogen precursor). Both the textural and the surface chemical properties of the support play an important role in the catalytic performance. Among the catalysts tested, the N-doped carbon nanotubes sample is the best support for this catalytic process, while the supports with high amounts of oxygen-containing surface groups decrease the catalytic performance of the metal phases.